2015
DOI: 10.1177/0748233714566877
|View full text |Cite
|
Sign up to set email alerts
|

Dibutyl phthalate induces oxidative stress and impairs spermatogenesis in adult rats

Abstract: Phthalates are abundantly produced plasticizers, and dibutyl phthalate (DBP) is the most widely used derivative in various consumer products and medical devices. This study was conducted to further explore the potential testicular toxicity of DBP in adult rats and to elucidate the underlying mechanisms. Adult male albino rats were treated orally with DBP at doses of 0, 200, 400, or 600 mg/kg/day for 15 consecutive days. Testicular weight, sperm count, and motility were significantly decreased. Treatment with D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
55
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 75 publications
8
55
0
4
Order By: Relevance
“…Several animal toxicology studies report that a number of phthalates are testicular toxicants and impair spermatogenesis (Aly et al ., 2015; Uren-Webster et al ., 2010). Based on results in several animal species DEHP and DBP metabolites appear to have the capacity to disrupt normal reproduction (semen quality, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Several animal toxicology studies report that a number of phthalates are testicular toxicants and impair spermatogenesis (Aly et al ., 2015; Uren-Webster et al ., 2010). Based on results in several animal species DEHP and DBP metabolites appear to have the capacity to disrupt normal reproduction (semen quality, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Some phthalates and phthalate metabolites have demonstrated anti‐androgenic properties in both animals and humans. Administration of the most commonly used plasticizer, dibutyl phthalate (DBP) to rats decreased serum FSH and testosterone levels, testicular weights, and sperm counts in a dose‐dependent manner (Aly et al ., ). Furthermore, these rats were found to exhibit increased oxidative stress and decreased antioxidant capacity within the testes along with associated testicular atrophy (Aly et al ., ).…”
Section: Ambient and Other Occupational Exposuresmentioning
confidence: 97%
“…Another study found that oral administration of various doses of DBP to adult male albino rats was associated not only with the hormone and semen changes already mentioned but also with a dose-dependent increase in seminal oxidative stress (reduced total antioxidant capacity) in comparison with healthy controls. Exposure to the highest doses (600 µg/kg) also provoked histological alterations to the seminiferous tubules, namely absence of spermatogenic cells in some of the tubules and tubular necrosis [74]. In a later study, adult male Wistar rats exposed to different concentrations of DBP via intraperitoneal injection presented dose-dependent seminal, steroidogenic and histological alterations with a reduction in the number of conceived embryos, an increase in abortions and a reduction in litter size compared with unexposed healthy controls [75].…”
Section: Postnatal Exposure: Are There Repercussions For Adult Testicmentioning
confidence: 99%